The Influence of Physical Exercise Behaviour on College Students' Mental Health - Kai Chuan; Yangming Xiong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This paper provides a comprehensive analysis of the current status of college students' mental health and the impact of physical exercise on their psychological well-being, covering various aspects including research quantity, research subjects, research methodology, research depth, and the underlying principles of sports intervention. The findings underscore the significant association between physical exercise and the modulation of college students' mental states, particularly in alleviating the stress induced by academic pressures. With the aim of investigating the determinants of college students' mental health, the author sought to examine the influence of physical exercise behaviour on their psychological well-being. A questionnaire survey was conducted among 730 undergraduate students from the 2021 cohort across eight conventional universities within a province. The participants comprised 400 males and 330 females, aged between 19 and 23 years. Regular physical exercise was operationally defined as engaging in physical activities more than three times per week, with a subset of 380 individuals (212 males and 168 females) exercising for durations exceeding 40 minutes each session. The study conducted an extensive literature review, consulting over 30 domestic and international sports and psychological journals to gather comprehensive and accurate background information. To assess the mental health profiles and attributes of the participants, the SCL-90 scale, a widely recognized general mental health questionnaire, was administered. Utilizing a combination of literature review, questionnaire administration, experimental inquiry, and mathematical statistical analysis, the author systematically examined the mental health status and physical exercise habits among college students within the province. The findings indicated an enhancement in adaptability, tolerance, self-control, cognitive abilities, social interaction skills, and overall well-being among the fifty subjects assessed across six dimensions of rehabilitation. By comparing these six indicators before and after the experiment, discernible improvements were observed, suggesting that engaging in physical activity significantly contributes to the enhancement of self-assessment across these dimensions. This underscores the pivotal role of physical exercise in fostering mental health improvement. There exists a significant correlation between physical exercise and the modulation of college students' psychological condition, with a positive impact on mitigating the psychological stress stemming from academic responsibilities. Consistent engagement in moderate physical exercise over the long term contributes to the enhancement of college students' mental well-being. Sustained participation in moderate-intensity physical activities yields beneficial effects on the enhancement of college students' mental health status.